Study on the mechanism of no. 8 burn ointment in burn treatment based on network pharmacology and experimental verification - Le Qiu; Danlei Xing; Yuanqiang Zhu; Zhiwei Zhuang; Yexiang Sun; Peng Gong; Xulin Chen (Frontiers in Pharmacology, 2025)
IntroductionAs a traditional Chinese compound formulation, No.8 burn ointment has demonstrated notable efficacy over half a century of clinical use, particularly in facilitating the healing of burn wounds.MethodsThis study integrates clinical data, liquid chromatography-mass spectrometry, network pharmacology and experimental validation to elucidate the mechanisms by which No.8 burn ointment promotes burn wound healing and to identify its key active components.ResultsThe findings reveal that the ointment may accelerate wound repair by modulating the HIF-1 signaling pathway. The network pharmacology analysis has identified HIF-1α as a core target of the No.8 burn ointment’s action and has identified the key active molecules β-Elemonic acid and Rubiadin, which interact with the HIF-1α protein and influence the HIF-1 pathway.ConclusionThis research not only provides a theoretical foundation for the selection of targeted drugs in burn treatment and the optimization of traditional Chinese compounds but also provides new ideas for future research in related fields.